How Does Advanced Technology Solve Unreliability Under Supply Chain Management Using Game Policy? - Suman Kalyan Sardar; Biswajit Sarkar (Mathematics, 2020)
Presently, it is essential to increase customer service such that the Supply Chain Management (SCM) can earn more profit in a sustainable manner. In the supply chain, the manufacturer and the retailer are two players who try to maintain the joint profit of the Supply Chain (SC) without only thinking about their own respective profits. However, the retailer may not provide all information to the manufacturer. This research introduces the use of the advanced technology Radio Frequency IDentification (RFID) in a retailer’s shop to obtain exact information about customer demand. A consignment policy is used to increase the manufacturer profit, and a fixed fee is offered to the retailer to generate more profit in coordination with the manufacturer. This study is conducted with and without the effect of RFID to show the benefit of SCM even when the retailer is unreliable. Both models are solved using the classical optimization technique. Numerical findings prove that SCM can benefit from the outcome of this study even for unreliability. Coordination within SCM can be maintained for a long time by using the proposed recommendations of this study.